How much money do spammers make from your website? - Hayati, P.; Firoozeh, N.; Potdar, Vidyasagar; Chai, K. (ACM, 2012)
Despite years of researcher’s contribution in the domain of spam filtering, the question as to how much money spammers can make has largely remained unanswered. The value of spam-marketing on the web can be determined by discovering the cost of distributing spam in Web 2.0 platforms, and the success ratio of turning a spamming campaign into a profitable activity. Currently, there is limited knowledge on the nature of spam distribution in web applications, and public methods for estimating the turnover rate for spammers, in the existing literature. Therefore, we adopted a methodological approach to address these issues and measure the value of spam-marketing on the web. Using current spam tactics, we targeted 66,226 websites both in English and non-English languages. We launched a spam campaign and set up a website to replicate spam practices. We posted spam content to 7,772 websites that resulted in 2059 unique visits to our website, and 3 purchase transactions, in a period of a month. The total conversion visit rate for this experiment was 26.49% and purchase rate was 0.14%.